2000
DOI: 10.1080/09537280050051979
|View full text |Cite
|
Sign up to set email alerts
|

Economic ordering policy of deteriorated item for vendor and buyer: An integrated approach

Abstract: This study develops an economic ordering policy of a deteriorating item with a constant production and demand rate. By considering the view of both the vendor and buyer, a mathematical model subject to single-vendor± single-buyer and multiple deliveries per order is developed. It can be shown that the integrated approach results in an impressive cost-reduction compared with an independent decision by the buyer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(58 citation statements)
references
References 5 publications
2
53
0
Order By: Relevance
“…The successful experiences of National Semiconductor, Wal-Mart, and Procter and Gamble have demonstrated that integrating the supply chain has significantly influenced the company's performance and market share (Simchi-Levi et al 2000). Other studies (Weng 1995;Li et al 1996;Yang and Wee 2000;Chen et al 2001) show that an integrated approach results in improved performance and increased profitability to all players in the supply chain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The successful experiences of National Semiconductor, Wal-Mart, and Procter and Gamble have demonstrated that integrating the supply chain has significantly influenced the company's performance and market share (Simchi-Levi et al 2000). Other studies (Weng 1995;Li et al 1996;Yang and Wee 2000;Chen et al 2001) show that an integrated approach results in improved performance and increased profitability to all players in the supply chain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ha and Kim [2] analyzed the integration between the buyer and the producer by setting up a mathematical model. Yang and Wee [3] derived the integration model between the producer and the buyer for deteriorating items. SARKER BR studied the influence of the shelve products' freshness on demand.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies ''D'' units of the product is demanded per unit of time. Mak (1982), Wee (1993), Wee (1998), Chung, Liu, and Tsai (1997), Abad (2000), Yang and Wee (2000), Rau, Wu, and Wee (2003), Yang (2004a), Dye, Ouyang, and Hsieh (2007), Ouyang, Teng, Goyal, and Yang (2009), Yang, Wee, Chung, and Ho (2010) consider constant rate of demand in their studies. Bhunia and Maiti (1998), Chung and Tsai (2001), Moon, Giri, and Ko (2005), Yang (2005) and Lee and Hsu (2009) assume the demand to be a time-dependent function.…”
Section: Introductionmentioning
confidence: 99%
“…Even though developing logistics models with a supply chain perspective makes the models more realistic, implementing these models is complicated and requires collaboration between the supply chain members. Yang and Wee (2000) and develop an inventory model for a two-echelon system with constant rate for demand and deterioration in which shortages are not allowed. develop a similar model with a difference in input pattern as the model is a production/inventory system.…”
Section: Introductionmentioning
confidence: 99%